2015
DOI: 10.1039/c5ra06371j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a novel PSf membrane containing rGO/PTh and its physical properties and membrane performance

Abstract: Recent advances in the fabrication of nanostructures such as graphene-related materials have received a lot of attention in membrane technology for the future of water supplies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The nanomaterials have also been explored recently to modify the surface properties of synthetic membranes. Different types of nanomaterials, such as SiO 2 , 35 TiO 2 , 36 ZrO 2 37 , 38 ( Figure 3 ), carbon nanotubes (CNT), 39 and graphene oxide (GO), 40 have been used as additives to different polymeric materials, such as cellulose acetate (CAc), PVDF, PA, PEI, and sulfone polymer, to achieve the desired functional properties. 41 Among inorganic nanomaterials, GO is one of the most appealing nanomaterials because of the presence of hydroxyl, epoxy, carbonyl, and carboxyl reactive species that provide high solubility in polar solvent with good colloidal properties, low toxicity, and a large surface area which can be useful for further modification.…”
Section: Physical and Chemical Characteristics Of Bioartificial Membr...mentioning
confidence: 99%
“…The nanomaterials have also been explored recently to modify the surface properties of synthetic membranes. Different types of nanomaterials, such as SiO 2 , 35 TiO 2 , 36 ZrO 2 37 , 38 ( Figure 3 ), carbon nanotubes (CNT), 39 and graphene oxide (GO), 40 have been used as additives to different polymeric materials, such as cellulose acetate (CAc), PVDF, PA, PEI, and sulfone polymer, to achieve the desired functional properties. 41 Among inorganic nanomaterials, GO is one of the most appealing nanomaterials because of the presence of hydroxyl, epoxy, carbonyl, and carboxyl reactive species that provide high solubility in polar solvent with good colloidal properties, low toxicity, and a large surface area which can be useful for further modification.…”
Section: Physical and Chemical Characteristics Of Bioartificial Membr...mentioning
confidence: 99%
“…Schematic illustration of the GO-PDI-modified α-Al 2 O 3 composite membrane preparation (Feng et al, 2016). Saf et al (Saf et al, 2015) synthesized a novel reduced graphene oxide/polythiophene (rGO/PTh) membrane employing in-situpolymerization as a simple and green synthesis method and incorporated it into polysulfone (PSF) via a phase inversion approach. The developed graphene membrane exhibited a microporous sponge-like structure, high porosity, and good hydrophilicity due to the addition of rGO/PTh nanocomposite.…”
Section: Graphene Based Composite Membranesmentioning
confidence: 99%
“…Additions of Fe 2 O 3 enhanced the membrane hydrophilicity but an increase in Fe 2 O 3 content caused a notable drop in the surface porosity of membrane. Furthermore, rejection studies were performed in (154). Inclusion of rGO/ PTh hybrid filler increased permeability and protein rejection.…”
Section: Hybrid Filler-based Mmmsmentioning
confidence: 99%
“…Inclusion of rGO/ PTh hybrid filler increased permeability and protein rejection. In this MMM, rGO added porosity to the membrane surface, while PTh enhanced hydrophilicity even though rGO alone is hydrophobic (154). A research by Teli et al demonstrated that MMMs containing hybrid fillers polyaniline (PANI)/phosphomolybdicacid (PMA) in PES offered a better antifouling activity and more efficient membranes than the simple PES membrane (155).…”
Section: Hybrid Filler-based Mmmsmentioning
confidence: 99%